Survey of period variations of superhumps in SU UMa-type dwarf novae. X. The tenth year (2017). (5th February 2020) - Kato, Taichi; Isogai, Keisuke; Wakamatsu, Yasuyuki; Hambsch, Franz-Josef; Itoh, Hiroshi; Tordai, Tamás; Vanmunster, Tonny; Dubovsky, Pavol A; Kudzej, Igor; Medulka, Tomáš; Kimura, Mariko; Ohnishi, Ryuhei; et al.
Abstract: Continuing the project described by Kato et al. (2009, PASJ, 61, S395), we collected times of superhump maxima for 102 SU UMa-type dwarf novae observed mainly during the 2017 season, and characterized these objects. WZ Sge-type stars identified in this study are PT And, ASASSN-17ei, ASASSN-17el, ASASSN-17es, ASASSN-17fn, ASASSN-17fz, ASASSN-17hw, ASASSN-17kd, ASASSN-17la, PNV J20205397+ 2508145, and TCP J00332502- 3518565. We obtained new mass ratios for seven objects using growing superhumps (stage A). ASASSN-17gf is an EI Psc-type object below the period minimum. CRTS J080941.3+ 171528 and DDE 51 are objects in the period gap, and both showed a long-lasting phase of stage A superhumps. We also summarize the recent advances in understanding of SU UMa-type and WZ Sge-type dwarf novae.